2015
DOI: 10.1016/j.bmc.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

γ-Benzylidene digoxin derivatives synthesis and molecular modeling: Evaluation of anticancer and the Na,K-ATPase activity effect

Abstract: Cardiotonic steroids (CS), natural compounds with traditional use in cardiology, have been recently suggested to exert potent anticancer effects. However, the repertoire of molecules with Na,K-ATPase activity and anticancer properties is limited. This paper describes the synthesis of 6 new digoxin derivatives substituted (on the C17-butenolide) with γ-benzylidene group and their cytotoxic effect on human fibroblast (WI-26 VA4) and cancer (HeLa and RKO) cell lines as well as their effect on Na,K-ATPase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Thus, the docking scores could be used potentially in the prediction of cytotoxicity of cardiac glycosides if they exert their bioactivity by targeting NKA directly. Additionally, it is worth noting that compound 9 showed the smallest docking scores (−11.8/−12.9 kcal/mol) and the most potent cytotoxicity against HeLa cells (IC 50 0.26 μM) [ 23 ], suggesting that this compound could be further modified structurally for the development of NKA-targeted antitumor agents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the docking scores could be used potentially in the prediction of cytotoxicity of cardiac glycosides if they exert their bioactivity by targeting NKA directly. Additionally, it is worth noting that compound 9 showed the smallest docking scores (−11.8/−12.9 kcal/mol) and the most potent cytotoxicity against HeLa cells (IC 50 0.26 μM) [ 23 ], suggesting that this compound could be further modified structurally for the development of NKA-targeted antitumor agents.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1 and 2 were purchased from Sigma-Aldrich (St. Louis, MO, USA), and compounds 3 – 6 , 10 , and 11 were prepared in the previous work by our group; the cancer cell cytotoxicity and molecular targets were already reported [ 19 , 31 ]. In turn, compounds 7 – 9 were selected from the literature, which also reported their bioactivities [ 23 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these synthetic digoxin analogues, 21-benzylidene digoxin (21-BD), presented cytotoxic and antiproliferative effects when used on HeLa cancer cells, via inducing apoptosis in those cells, but inhibiting NKA activity just at high micromolar levels 18 , 19 . Subsequently, starting with the structure of digoxin, we synthesised a series of γ-benzylidene derivatives and showed that they have cytotoxic effects on HeLa and RKO cancer cell lines that are independent from the modulation of NKA activity 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Alves et al synthesized digoxin derivatives of butenolide with a benzylidene at C-4 of the lactone ring (Figure 32) [134]. The substituent on the aromatic ring had an influence on the antiproliferative activity, and the 4-(dimethylamino)benzylidene derivative of digoxin ( 85a ) showed the most potent activity on HeLa and colon carcinoma (RKO) cells, as well as human lung fibroblasts (WI-26 VA4) (Table 32).…”
Section: Antitumor and Antiviral Activities Of L-ascorbic Acid Dermentioning
confidence: 99%